Accelerated Corrosion Tests in Quality Labels for Powder Coatings on Galvanized Steel—Comparison of Requirements and Experimental Evaluation - Izabela Kunce (MDPI AG, 2021)
Powder coatings are widely applied for corrosion protection of steel, aluminum, and hot dip galvanized steel in a variety of corrosive environments. Powder coatings are subjected to a number of strict laboratory tests to determine their mechanical properties, corrosion resistance, and color stability. Among European quality certificates for powder coatings applied to galvanized steel, the most commonly recognized are GSB-ST and Qualisteelcoat certificates, which also refer to the EN 13438 standard. Certificates of quality for powder coatings are constantly updated according to the latest research results and experience of specialists operating in the field of corrosion protection. This paper presents an experimental evaluation of how the required length of selected accelerated corrosion tests can affect the final assessment of powder coatings. On the example of two powder painting systems: polyester as well as based on epoxy and polyester resins, the paper presents the influence of the time of accelerated corrosion tests: ISO 6270, ISO 9227 (Neutral Salt Spray and Acetic Acid Salt Spray), and ISO 3231 on the protective properties of the coatings. The results of damage assessment according to ISO 4628 have been correlated with the requirements of particular quality specifications. Additionally, based on FTIR (Fourier Transform Infrared Spectroscopy) and EIS (Electrochemical Impedance Spectroscopy) analyses, the influence of the applied corrosion tests on the degradation degree of the coatings studied has been presented. The paper aims to present a tests for those powder coating systems applied to facilities for which the main requirement is corrosion resistance rather than aesthetics.